DINAMIKA KEHIDUPAN SOSIAL-BUDAYA MASYARAKAT MINANGKABAU DALAM NOVEL GERHANA KARYA A.A NAVIS - Siska Darma Sari; Nurizzati Nurizzati; Bakhtaruddin Nasution (Faculty of Languages and Arts, Universitas Negeri Padang, 2014)
This study hasseveral objectives, namely: (1) describethe dynamics ofsocio-cultural life of Minangkabau society in the novel Eclip seprimary group A.A Navis works, (2) describethe dynamics of socio-cultural life of Minangkabau society in the novel Eclip secondary group A.A Navis works, (3) describe the dynamics ofsocio-cultural life of Minangkabau societyinthe novel Eclip seformal group A.A Navis works, (4) describethe dynamics ofsocio-cultural life of Minangkabau society in the novel Eclip seinformal group A.A Navis works. The data of this studyis thesocio-cultural dynamics of Minangkabau societycontainedin the novel Eclipse A.A Navis works. Subjects of this studyis the researchers them selvesw hoassisted withthe data iventaris format. Data validationtechniquesusedin this studyisa detailed description of the technique. The findings of this study are socio-cultural dynamics within the group, secondary, formaland informal.